Students of Preschool Education Programs in the Face of Latin American Immigration in Chile - María José Mera-Lemp (Universidad Autónoma de Baja California, 2021)
The increase in the enrollment of immigrant children is posing new challenges for preschool education in Chile. Despite this, few studies have examined the attitudes of educators towards Latin American immigrants as well as other variables that may impact these attitudes. This exploratory research sought to analyze the relationships between out-group threat, cultural self-efficacy and affective prejudice in a sample of 153 students of preschool education. In addition, an attempt was made to determine the extent to which the perceived out-group threat and cultural self-efficacy explain this prejudice. The results show that the perception of out-group threat and cultural self-efficacy explain 34.4% of variability in the participants’ affective prejudice. The relevance of these results for students’ education is discussed.